Giuseppe Pagano : design for social change in fascist Italy - Marcello, Flavia (Intellect Books, 2020)
This book provides a comprehensive overview of the influential architect Giuseppe Pagano and his contribution to the development of modern architecture. With chapters by Tim Benton, Noa Steimatsky, Cesare de Seta, Caterina Franchini and Claudia Cagneschi.